METAVERSE DISRUPTION IN PUBLIC SERVICES: OPPORTUNITIES AND CHALLENGES IN BUILDING VIRTUAL GOVERNMENT IN WEST TULANG BAWANG DISTRICT - Fitri Wahyuni (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study examines the disruption of the metaverse in public services, with a focus on the opportunities and challenges of building a virtual government in Tulang Bawang Barat Regency. The metaverse has emerged as a potential frontier in digital government transformation, offering immersive and interactive platforms for service delivery. However, its adoption in local government contexts, particularly in regions with medium digital maturity, remains underexplored. Using a qualitative approach with descriptive analysis, this study integrates secondary data from SPBE index assessments, demographic statistics, and policy documents, alongside a literature review on metaverse governance. Findings indicate that Tulang Bawang Barat has laid initial foundations for digital government through SPBE implementation. Nevertheless, three major gaps constrain metaverse adoption: digital infrastructure deficits, human resource capability gaps, and the absence of regulatory frameworks for virtual governance. The study concludes that building a virtual government requires a phased approach prioritizing foundational digital transformation before metaverse integration. Strategic recommendations include strengthening digital infrastructure, developing public sector digital competencies, and establishing ethical guidelines for virtual service delivery.